Artificial liver plasma adsorption improves survival in elderly patients with severe pneumonia: a retrospective cohort study - Chen, Richai; Jin, Jiaqian; Zhang, Sainan; Wu, Jiajun; Xiang, Qiangqiang; Lin, Xuanhao; Zhu, Danhua; Zhu, Mengfei (Frontiers in Medicine, 2025)
ObjectiveTo assess the therapeutic efficacy of artificial liver plasma adsorption (ALPA) in patients with severe pneumonia.MethodsThis retrospective study enrolled 151 patients meeting severe pneumonia diagnostic criteria who were admitted to the intensive care unit at Shulan Hospital, Hangzhou, China, between January 2020 and December 2024. Participants were allocated to either: (1) the ALPA intervention group (n = 56) receiving artificial liver plasma adsorption (ALPA) therapy, or (2) the control group (n = 95) receiving standard treatment. This study prospectively collected comprehensive clinical data, including: (1) baseline demographic characteristics; (2) serial measurements of laboratory parameters (e.g., white blood cell count (WBC), lymphocyte percentage (LY%), C-reactive protein (CRP), procalcitonin (PCT), and interleukin-6 (IL-6)) at pre- and post-treatment intervals; and (3) Pneumonia Severity Index (PSI) scores at admission. Patient survival outcomes were systematically recorded, including: (1) time-to-event endpoints (overall survival duration from enrollment to death or last follow-up), and (2) clinical outcomes.ResultsNo statistically significant differences were observed between the two groups regarding WBC, CRP, PCT, or IL-6 levels at baseline (all p ≥ 0.05). However, the LY% in the artificial liver treatment group was significantly lower compared to the conventional therapy group (p < 0.05). Post-treatment analysis revealed that the ALPA group demonstrated significantly lower levels of WBC, LYM, CRP, PCT, and IL-6 compared to control group (p < 0.05). The control group exhibited significant post-treatment elevations in WBC (p < 0.05), whereas LY%, PCT, IL-6, and CRP levels showed no significant variation (p ≥ 0.05). In the ALPA group, WBC, LY%, and PCT levels remained stable (p ≥ 0.05), while CRP, IL-6 demonstrated a significant reduction (p < 0.05). Post-treatment mortality rates differed significantly between groups (42.9% in ALPA group versus 81.1% in controls; p < 0.001). The treatment group showed a 38.2% relative reduction in mortality compared to controls, achieving statistical significance (p < 0.001). Multivariable Cox proportional hazards regression demonstrated that both elevated PSI Score at hospital admission (adjusted HR = 1.009, p = 0.006) and ALPA treatment (adjusted HR = 4.134, p < 0.001) independently predicted poorer survival outcomes. ALPA treatment was associated with significantly improved survival outcomes compared to controls (mean: 218.42 vs. 36.81 days; median not reached vs. 27.0 days; HR = 0.1907, p < 0.0001 by log-rank test).ConclusionArtificial liver plasma adsorption (ALPA) therapy demonstrates significant clinical efficacy by effectively suppressing inflammatory markers (e.g., IL-6, CRP) and attenuating cytokine storm progression. This treatment significantly reduces mortality and prolongs survival time in elderly patients with severe pneumonia.